Population Impact of Drug Interactions with Warfarin: A Real-World Data Approach - Martín-Pérez, Mar; Gaist, David; de Abajo, Francisco J.; Rodríguez, Luis A. García (Thrombosis and Haemostasis, 2018)
Objective To investigate the population impact of previously reported interactions between warfarin and other drugs on international normalized ratio (INR) levels.Methods Using The Health Improvement Network (THIN), a United Kingdom primary care database, a cohort of warfarin users between 2005 and 2013 (N = 121,962) was followed until the first qualifying prescription for the potential interacting drugs was evaluated. Sixteen sub-cohorts, one for each study drug, and a control sub-cohort of warfarin were ascertained. Short-term changes in INR levels were assessed by comparing INR values measured before and after initiation of the interacting drug with paired Student's t-test. We also evaluated the proportion of patients with INR values outside the therapeutic range (INR: 2–3).Results Miconazole use was associated with the highest mean increase in INR (+3.35), followed by amiodarone (+1.28), fluconazole (+0.79), metronidazole (+0.75) and nystatin (+0.65). After subtracting the natural INR variation observed in the control sub-cohort, supra-therapeutic levels (INR > 3) were found in 53.2% (miconazole), 45.5% (amiodarone), 23.3% (metronidazole), 23.2% (fluconazole) and 17.6% (nystatin) of patients initiating treatment with these drugs. Carbamazepine use was associated with a mean INR decrease of –0.63 and infra-therapeutic levels (INR < 2) were observed in 46.2% of patients initiating carbamazepine. For all other drugs, the change was small to moderate, in absolute INR units (+0.23 to +0.55) and in the proportion of patients with INR levels out of therapeutic range (<16%).Conclusions Clinically potentially important interactions were observed in several study drugs. The majority of them, although confirmed, had little impact after adjusting for standard INR variability in the general population of warfarin users.
Keywords: anticoagulant drugs; warfarin; drug interactions; INR; database